Economic burden of chronic obstructive pulmonary disease in Morocco: a cost of illness study - Soumaya Benmaamar; Btissame Es-sabbahi; Mohammed Taghyioullah Haiba; Mohamed Omari; Ibtissam El Harch; Mohammed Youbi; Latifa Belakhhel; Loubna Abousselham; Hafid Hachri; Imane El Menchawyi; Samira EL Fakir; Mohammed Chakib Benjelloun; et al. (Monaldi Archives for Chest Disease, 2024)
Chronic obstructive pulmonary disease (COPD) carries an important economic burden worldwide. However, the cost of this disease in Morocco is not well explored. This study aimed to estimate the economic cost associated with COPD in Morocco and identify its determinants. A cost of illness, prevalence-based study using a bottom-up approach method, including COPD patients, was carried out in 2021-2022. The cost was estimated from a societal perspective, and the time horizon was 1 year. Data collection was performed using a questionnaire including socio-demographic, clinical data, and utilization of health care resources in 2019: hospitalization, medical tests, medications, and medical visits. Direct health cost (DHC) was estimated by multiplying the use of health services by the official prices (unit costs) published by the National Agency for Health Insurance. The indirect cost (IC) represented by labor productivity losses was calculated using the human capital method. Costs were compared according to different socio-demographic and clinical factors. We included 159 patients; 82.4% were men, 80.4% were current or former smokers, and 78.7% were categorized as “high-risk” groups (grades C–D). The DHC was estimated at $1816.6 per patient per year. Pharmaceutical and hospitalization costs represented the highest part of the total DHC (42.5% and 22.1%, respectively). The IC was estimated at $709.5±1081.3 per patient per year. DHC increased with increasing disease severity and with the number of severe exacerbations (p<0.001). Current and former smokers were more costly to the healthcare system than nonsmokers (p=0.029). IC also increased with the number of severe exacerbations (p=0.003). In this study, we showed that COPD in Morocco generates important costs for the health system, mainly related to smoking and the severity of the disease. It is therefore important to strengthen tobacco control measures in our country.